2022
DOI: 10.1039/d2tc00803c
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-enhanced spin–orbit coupling in a quantum anomalous Hall insulator Fe2Br2 monolayer with a large band gap and robust ferromagnetism

Abstract: Nontrivial band topology combined with magnetic ordering can produce quantum anomalous Hall insulator (QAHI), which may lead to advances in device concepts. Here, through first-principles calculations, stable monolayer $\mathrm{Fe_2Br_2}$ is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…18,19 Numerous theoretical studies confirmed that these Janus monolayer materials have great potential for applications in optoelectronic, 20,21 photocatalytic, 22,23 spintronic, [24][25][26] thermoelectric, 27,28 piezoelectric, [29][30][31][32] and valleytronic 33 devices. Recently, inspired by the prediction that Fe 2 X 2 (X = I or Br) monolayers are room-temperature ferromagnets 34,35 with excellent carrier mobility, tunable perpendicular magnetic anisotropy, graphene-like Dirac bands and exotic topological phases, Guo et al investigated the Janus monolayers Fe 2 IY (Y = Cl and Br) and theoretically confirmed that they are piezoelectric quantum anomalous Hall insulators (PQAHI) resulting from inversion symmetry breaking. 36 Furthermore, Fe 2 I 1−x Br x (x = 0.25 or 0.75) monolayers with M x and M y mirror symmetries were confirmed to preserve the topological properties.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Numerous theoretical studies confirmed that these Janus monolayer materials have great potential for applications in optoelectronic, 20,21 photocatalytic, 22,23 spintronic, [24][25][26] thermoelectric, 27,28 piezoelectric, [29][30][31][32] and valleytronic 33 devices. Recently, inspired by the prediction that Fe 2 X 2 (X = I or Br) monolayers are room-temperature ferromagnets 34,35 with excellent carrier mobility, tunable perpendicular magnetic anisotropy, graphene-like Dirac bands and exotic topological phases, Guo et al investigated the Janus monolayers Fe 2 IY (Y = Cl and Br) and theoretically confirmed that they are piezoelectric quantum anomalous Hall insulators (PQAHI) resulting from inversion symmetry breaking. 36 Furthermore, Fe 2 I 1−x Br x (x = 0.25 or 0.75) monolayers with M x and M y mirror symmetries were confirmed to preserve the topological properties.…”
Section: Introductionmentioning
confidence: 99%
“…7(b) displays the collection of band gaps of previously reported 2D QAHE materials. 13,23,62–69 The results indicate that the SOC induced global band gap of PdTaTe 2 (566 meV) is the largest one (the 798 meV band gap is not global one 69 ) in the ferromagnetic Chern insulators reported to date. A detailed comparison can also be found in Table S2 (ESI†).…”
Section: Conclusion and Discussionmentioning
confidence: 90%
“…Moreover, edge states of PdTaX 2 (X = Se, Te) are totally spin-polarized, and they are also potential candidate for spintronics. For more comparison, we collect T c values from previously synthesized and theoretically predicted 2D Chern insulators, 13,23,[62][63][64][65][66][67][68] especially those belonging to the same tetragonal crystal structure, 13,23,[66][67][68] and the monolayers we proposed, the comparison is presented in Fig. 7(a).…”
Section: Conclusion and Discussionmentioning
confidence: 99%